The Role of MSME in Growth of Employment in India - K.V, Deepa; Mathew, Rincy V (International Journal of Psychosocial Rehabilitation, 2020)
Micro, Small, Medium Enterprise is the backbone of Indian economy. The MSME plays a vital role in generation of employment opportunities. The MSME providing employment opportunities more than 6 crore people. And also it providing 65% share of employment in urban area and 45% in rural areas. The MSME are widening their domain across sectors of the economy, producing diverse range of products and services to meet demands of domestic as well as global market. So this paper is an attempt to find out the role of MSME in growth of employment in India.